Study of Physics-Based preconditioning with High-order Galerkin discretization for hyperbolic wave problems - Courtès Clémentine; Franck Emmanuel; Helluy Philippe; Oberlin Herbert (ESAIM: Proceedings and Surveys, 2016)
In this article, we detail the construction of a physics-based preconditioner. The Schur decomposition is the key point of the method which is tested on two hyperbolic systems : acoustic wave equations and shallow water equations without source term. Some conserved properties between preconditoner and initial operator are discussed, especially the propagation speeds of a plane wave.